The race of the Birkebeiners - Lunge-Larsen, Lise (Houghton Mifflin, 2001)
Tells how the infant Prince Hakon is rescued by men fiercely loyal to his dead father, who ski across the rugged mountains in blizzard conditions to save him from his enemies, the Baglers.